(untitled) (BIRDEM Medical Journal, 2021)
Background: Home-based palliative care (HPC) is a community-based palliative care approach with various advantages over institutional care like comprehensive care at patient’s known comfortable environment. This study aims at describing a pilot HPC program. Methods: A 3-year pilot project was implemented by Centre for Palliative Care (CPC) of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, supported by the Ministry of Education. At the end of the project period the team attempted a survey to capture a picture of HPC recipients, of their suffering and their needs and to assess as to what extent these needs can be met in the best possible way with the present strategy. A total of 34 patients and their caregivers were interviewed over telephone about receiving homecare. An attempt was taken to compare with the patients who used to get conventional care along with an access to the 24/7 telephone care service. Results: A total of 1634 home visits were made to 338 patients, mostly (79.3%) to 310 cancer patients and covered 0.807% of estimated population in need of palliative care in Dhaka City Corporation. Pain was the most prevalent symptom and opioid drugs were the most commonly prescribed medication. HPC helped them to remain at their own home where they wanted to be and assisted them taking into account individually tailoring care and enabled them to continue coping. Conclusions: HPC helped the patients of incurable diseases and their families to avail comprehensive care at home contributing to reduce hospital burden. Enhancement of the care infrastructure will ensure a sustainable provision of palliative care in the domestic environment. BIRDEM Med J 2021; 11(3): 202-211